Produksi gula cair dari selulosa kulit buah naga merah (hylocereus polyrhizus) dengan hidrolisis enzim - Nuraini, Michelle Nattaya Narerat; Mutma'innah, Mustika Nindiya; Tridayanti, Devi; Hartanti, Lucky (Journal of Agritechnology and Food Processing, 2022)
Liquid sugar is a sweetener that is widely used in the food industry. Apart from starch, liquid sugar can be produced from cellulose hydrolysis by using cellulase enzymes. This study aims to obtain the best concentration of cellulase enzymes in the production of cellulose liquid sugar in the skin of red dragon fruit. The production of liquid sugar uses the method of hydrolysing enzymes of different concentrations (1%,2%,3%). The results showed that there was no significant influence on the characteristics of liquid sugars resulting from the addition of three different enzyme concentrations. The observed characteristics are total sugar content, water, ash content, viscosity and color. Enzyme concentration of 3% is the best liquid sugar based on observations of total sugar content and color.